Analyzing Content An ESP Textbook: English International Tourism By Peter Strutt - Abdul Syahid; Siti Rahimah; Fajariah Fajariah; Rini Listiya Ningrum; Krisna Dwi Alifhia Rezky (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aimed to analyze the content of the English textbook